Programming Interviews For Dummies - Sonmez, John Z.; Butow, Eric (Tantor Media, Inc., 2020)
Get ready for interview success Programming jobs are on the rise, and the field is predicted to keep growing, fast. Landing one of these lucrative and rewarding jobs requires more than just being a good programmer. Programming Interviews For Dummies explains the skills and knowledge you need to ace the programming interview. Interviews for software development jobs and other programming positions are unique. Not only must candidates demonstrate technical savvy, they must also show that they're equipped to be a productive member of programming teams and ready to start solving problems from day one. This book demystifies both sides of the process, offering tips and techniques to help candidates and interviewers alike. It will enable you to: prepare for the most common interview questions; understand what employers are looking for; develop the skills to impress non-technical interviewers; learn how to assess candidates for programming roles; and prove that you (or your new hires) can be productive from day one. Programming Interviews For Dummies gives listeners a clear view of both sides of the process, so prospective coders and interviewers alike will learn to ace the interview.